The Functionality of Cross Training Practitioners - Sousa, Jéssica Aparecida Pedroso de; Garros, Danielle dos Santos Cutrim (Seven Editora, 2023)
Cross Training is a strength and fitness program, with constantly varied exercises, high intensity, and functional movements. Compared to other contact sports such as soccer, judo, and basketball, this type of training does not have higher rates of injuries. The objective was to present functional aspects of the upper limbs of individuals practicing "Cross Training". Methodology: 19 individuals between 20 and 59 years of age, Cross training practitioners with a minimum time of 6 (six) months of practice were included. As exclusion criteria, individuals who presented some lesion at the time of data collection. The following instruments were used for data collection: an upper limb dynamometer to assess handgrip strength; a goniometer to measure the range of motion of the shoulder, elbow, and wrist joints; a test of the box and blocks for evaluation of manual dexterity. Conclusion: the practitioners presented good fine motor coordination and handgrip strength, however, 42% of the practitioners presented hyper-medial rotation of the elbow, however, the data collected showed a good range of motion of the shoulder of these individuals. DOI:https://doi.org/10.56238/alookdevelopv1-038